The Effect of Limestone Variations on the Compressive Strength of Clay Soil Stabilized with Pumice Microsilica and Aluminum Hydroxide - A. Majid, Budiman; Gaus, Abdul; Adriaty, Yolly; Helda Evita Putri; Rauf, Ichsan (UIR PRESS, 2026)
The pozzolanic reaction is a chemical interaction involving calcium hydroxide, silica, and alumina that contributes to the chemical stabilization of soil. An optimized proportion of these three components can yield greater improvements in soil strength compared to the use of a single stabilizing material. This research examines the additional effect of limestone as a calcium source on clay soil stabilized with pumice-based microsilica and hydroxide aluminate. The testing of soil properties in this research follows the American Society for Testing Materials (ASTM) guidelines. The stabilization materials used include pumice, hydroxide aluminate, and limestone. The mechanical behavior of the blend of these three minerals is determined from the findings of the unconfined compressive strength tests, using cylindrical test samples measuring 35 mm in diameter and 70 mm in height. Variations in the addition of lime used to form the mixed matrix were 2%, 4%, and 6% by weight of dry soil. Laboratory test results showed a very significant increase in unconfined compressive strength (qu) compared to natural soil or soil stabilized only with silica and alumina. The optimum value for lime addition in this mixture was 4%, which resulted in a qu value of 52.48 kg/cm².